L-N-acetylcysteine protects outer hair cells against TNFα initiated ototoxicity in vitro. - Tillinger, Joshua A.; Gupta, Chhavi; Ila, Kadri; Ahmed, Jamal; Mittal, Jeenu; Van De Water, Thomas R.; Eshraghi, Adrien A. (Acta Oto-Laryngologica, 2018)
Objective: The present study is aimed at determining the efficacy and exploring the mechanisms by which L-N-acetylcysteine (L-NAC) provides protection against tumor necrosis factor-alpha (TNFα)-induced oxidative stress damage and hair cell loss in 3-day-old rat organ of Corti (OC) explants. Previous work has demonstrated a high level of oxidative stress in TNFα-challenged OC explants. TNFα can potentially play a significant role in hair cell loss following an insult to the inner ear. L-NAC has shown to provide effective protection against noise-induced hearing loss in laboratory animals but mechanisms of this otoprotective effect are not well-defined. Design: Rat OC explants were exposed to either: (1) saline control (N = 12); (2) TNFα (2 μg/ml, N = 12); (3) TNFα+L-NAC (5 mM, N = 12); (4) TNFα+L-NAC (10 mM, N = 12); or (5) L-NAC (10 mM, N = 12). Outer hair cell (OHC) density, levels of reactive oxygen species (ROS), lipid peroxidation of cell membranes, gluthathione activity, and mitochondrial viability were assayed. Results: L-NAC (5 and 10 mM) provided protection for OHCs from ototoxic level of TNFα in OC explants. Groups treated with TNFα+L-NAC (5 mM) showed a highly significant reduction of both ROS (p < 0.01) and 4-hydroxy-2-nonenal immunostaining (p < 0.001) compared to TNFα-challenged explants. Total glutathione levels were low in TNFα-challenged explants compared to control and TNFα+L-NAC (5 mM) treated explants (p < 0.001). Conclusions: L-NAC is a promising treatment for protecting auditory HCs from TNFα-induced oxidative stress and subsequent loss via programmed cell death.